Retrofit of Diesel Engines with H2 for Potential Decarbonization of Non-Electrified Railways: Assessment with Lifecycle Analysis and Advanced Numerical Modeling - Mehrshad Kolahchian Tabrizi; Tarcisio Cerri; Davide Bonalumi; Tommaso Lucchini; Morris Brenna (Energies, 2024)
The application of hydrogen in heavy-duty vehicles or trains has been suggested as a promising solution to decarbonize the transportation sector. In this study, a one-dimensional engine modeling is employed to evaluate the potential of hydrogen as a fuel for railway applications. A turbocharged diesel engine is simulated as the baseline unit, and the results are validated with experimental data. The same engine is converted to become compatible with hydrogen through some modifications in the turbocharger group and the injection and ignition systems to preserve the performance of the baseline configuration. The findings show that the engine traction power is reduced from 600 to 400 kW, indicating an inferior performance for the hydrogen-fueled engine. The energy consumption of the hydrogen-fueled engine on a real train mission profile is almost two times the diesel version. However, our Life Cycle Assessment analysis with a Well-to-Wheel system boundary shows a 56% reduction in equivalent CO2 emissions for the engine fueled with photovoltaic-based green hydrogen. Substituting diesel with low-carbon hydrogen can decrease the train’s carbon footprint from 4.27 to even less than 2 kg CO2 eq./km, suggesting that moderately modified engines are a promising solution for decarbonizing non-feasibly electrified railway sections.